Design and Implementation of Automatic Fan Control System Based on Room Temperature Using Microcontroller-Based LM35 Sensors - Aditiawarman, Rangga; Tasmi; Teary, Muhammad Gald (Program Studi Teknologi Informasi, Fakultas Teknik, Universitas Udayana, 2025)
Room temperature control is an important aspect in maintaining user comfort and ensuring the efficient performance of electronic devices in enclosed spaces. Manual fan operation is considered ineffective because it cannot respond promptly to temperature changes and may lead to energy inefficiency. Therefore, this study aims to design and implement an automatic fan control system based on room temperature using an LM35 temperature sensor and an Arduino Uno microcontroller. The control method applied is threshold-based control, in which the fan automatically turns on or off according to a predefined temperature limit. The system consists of an LM35 sensor for temperature sensing, a microcontroller for data processing, a relay module as the actuator controller, a DC fan as the cooling device, and an I2C-based LCD as the display unit. System testing was conducted in an enclosed room with naturally varying temperature conditions. The experimental results show that the system is capable of reading room temperature stably and in real time, displaying temperature data clearly, and controlling the fan automatically and consistently according to the room temperature conditions. Based on its performance, the proposed system can be considered a simple, efficient, and easily applicable solution for room temperature control in small- to medium-scale enclosed environments. Keywords: temperature control, automatic fan, LM35 sensor, microcontroller, embedded system.